Computing Swedish Salafism: An Example of a Digital Humanities Approach to Collecting, Organizing, and Analyzing Data on Web-based Salafi Missionary Activity in Sweden - Svensson, Jonas (Journal of religion in Europe, 2020)
The aim of this article is to exemplify how computer-aided methods can assist researchers in the study of religions to collect, organize, and perform rudimentary analysis on web-based material. For this, the article uses the case of the Swedish Salafi website darulhadith.com, perhaps the largest provider of Islamic texts in Swedish online. The results show how the computer-aided methods can greatly facilitate the gathering of information on publication patterns and affiliations that can serve as a basis for further, in-depth studies of content and context. The article discusses possible avenues for assessing levels of impact and suggests further ways in which the content of the material gathered can be explored using computer-aided methods.